The global and national perspective of women’s education on breastfeeding - Kowalska, Marta Estera; Kalinowski, Paweł; Bojakowska, Urszula (Nursing in the 21st Century, 2013)
THE GLOBAL AND NATIONAL PERSPECTIVE OF WOMEN’S EDUCATION ON BREASTFEEDING Breastfeeding of an infant and a child plays a key role in proper physical and intellectual development. Widespread changes in lifestyle and environmental factors modify behaviour of women who give up breastfeeding or shorten the feeding time, without taking account of the recommendations about breastfeeding a baby until at least 6 months of age. It is, therefore, necessary to conduct educational activities in societies. The purpose of this paper is to present global and national activities and recommendations about the women’s education on breastfeeding. The implementation of the tasks concerning the women’s education on advantages and disadvantages of breastfeeding should be done starting from the highest level - the government of the country through educational campaigns by NGOs and the media – and ending with individual actions taken by breast clinics.